Pentingnya literasi digital dalam membangun pribadi yang berkarakter pancasila - Primayditha, Nazwa; Devi, Raihan; Adhiyya, Sania Fawwaiza (Maliki Interdisciplinary Journal, 2024)
Pancasila as the ideology of the Indonesian state is not just a symbol or emblem of the state. It originates from the values ​​of the Indonesian nation that have existed for a long time which were then crystallized into the nation's ideology as the foundation/guidelines and hopes of the entire Indonesian nation to realize a prosperous life. To become a person with Pancasila character, people must first understand the values ​​contained therein. Literacy culture, both conventional and digital, allows Indonesian people to deepen their knowledge of Pancasila, which makes it a good habit and action or behavior that is in line with Pancasila values. A digital literacy culture will encourage the younger generation to form a creative and critical mindset in dealing with current issues. By cultivating literacy, it will also help people get accurate and quality information. Applying Pancasika in the era of digital technology. Nowadays, thanks to the development of information technology, we can quickly connect with anyone and anywhere. For example, to communicate quickly with friends or other people and connect to the Internet just with a cellphone, laptop or computer. The development of information technology can be called digital technology. The development of information technology certainly played a role in the realization of Pancasila. The development of digitaltechnology makes it easier to communicate with people from various places, thus providing opportunities to introduce values ​​and traditions that reflect Pancasila to more people. Various forms of social media are the result of developments in digital technology that can be used to combat behavior that reflects Pancasila.